Social determinants of health and disease: the role of small-scale projects illustrated by the Koster health project in Sweden and Ametra in Peru Determinantes sociais de saúde e doença: o papel de pequenos projetos em saúde ilustrado pelos projetos Koster na Suécia e Ametra no Peru - Maj-Lis Follér (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 1992)
Two different health projects are evaluated in this paper. The Koster Health project taking place at the Koster Islands in Sweden and the Ametra project going on among the Shipibo-Conibo in Peru. Both projects focus more on the determinants of health than on sickness and more on the individual's subjective feeling of illness than on the biomedically "objectively" recognizable disease. "Mobilization" and "responsibility"for the individual's own health are central concepts in both projects. In the theoretical part of the paper a human ecological perspective is suggested to analyse the interaction between human health and environmental changes. The author emphasizes the importance of interdisciplinary research when evaluating how the external determinants from the natural and social environment affect human beings and health. The human ecological approach is seen as a complement to the biomedical research. Health and disease are two poles in a continuum. In a pluralistic society we should struggle towards the pole of health. Este artigo revê e avalia dois projetos de saúde - o Koster Health Project realizado nas ilhas Koster, Suécia, e o Ametra Project, realizado entre os indígenas Shipibo-Conibo, Peru. Ambos enfocam, principalmente, os determinantes de saúde, ao invés da doença. Os projetos também privilegiam em suas abordagens os sentimentos subjetivos individuais sobre a doença, ao invés de doenças "objetivamente" reconhecidas pela biomedicina. "Mobilização" e "responsabilidade" pela saúde do próprio indivíduo são conceitos centrais em ambos os projetos. O artigo busca na ecologia humana o suporte teórico para analisar a interação entre saúde humana e mudanças ambientais. A autora enfatiza a importância da pesquisa interdisciplinar na avaliação do papel exercido pelos fatores naturais e sociais sobre os seres humanos e a saúde. A abordagem da ecologia humana é vista como complementar à pesquisa biomédica sendo, saúde e doença, concebidas como dois pontos em um continuum. A autora argumenta que em uma sociedade pluralista deve-se lutar no sentido de se avançar rumo ao polo da saúde.